Examining the Relative Roles of Domestic and Foreign Direct Investments in Nigeria - Osabuohien, Evans S.; Soogun, Ayobami O.; Urhie, Ese (International Journal of Economics and Financial Issues, 2017)
This study examines the relative relevance of domestic investment (DI) and foreign direct investment (FDI) on economic performance in Nigeria (1980-2014). In an attempt to achieve this broad objective, annual time series data sourced from the Central Bank of Nigeria (CBN)'s Statistical Bulletin, which was estimated using Vector Error Correction (VEC) technique, among others. The results, inter alia, show that both DI and FDI had significant effect on Nigeria's economic performance; however, the influence of the former was observed to be far greater than the latter with marked difference both in terms of the level of significance and size. Thus, the study recommends, among others, the need for government to create the ambience that will enable domestic investors to thrive, on one hand, and be complemented by foreign investment, on the other. Keywords: Domestic investment, Foreign direct investment, Economic performance, Vector error correction model JEL Classifications: F21; F23